A Comparative Study of Ground and Underground Vibrations Induced by Bench Blasting - Xiuzhi Shi; Xianyang Qiu; Jian Zhou; Dan Huang; Xin Chen; Yonggang Gou (Shock and Vibration)
Ground vibrations originating from bench blasting may cause damage to slopes, structures, and underground workings in close proximity to an operating open-pit mine. It is important to monitor and predict ground vibration levels induced by blasting and to take measures to reduce their hazardous effects. The aims of this paper are to determine the weaker protection objects by comparatively studying bench blasting induced vibrations obtained at surface and in an underground tunnel in an open-pit mine and thus to seek vibration control methods to protect engineering objects at the site. Vibrations arising from measurement devices at surface and in an underground tunnel at the Zijinshan Open-Pit Mine were obtained. Comparative analysis of the peak particle velocities shows that, in the greatest majority of cases, surface values are higher than underground values for the same vibration distance. The transmission laws of surface and underground vibrations were established depending on the type of rock mass, the explosive charge, and the distance. Compared with the Chinese Safety Regulations for Blasting (GB6722-2014), the bench blasting induced vibrations would not currently cause damage to the underground tunnel. According to the maximum allowable peak particle velocities for different objects, the permitted maximum charges per delay are obtained to reduce damage to these objects at different distances.